2013
DOI: 10.1097/mlr.0b013e3182992c5a
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Preventable Use of Emergency Services

Abstract: Background Limited health literacy is a barrier to understanding health information and has been identified as a risk factor for overuse of the emergency department (ED). The association of health literacy with access to primary care services in patients presenting to the ED has not been fully explored. Objective To examine the relationship between health literacy, access to primary care and reasons for ED use among adults presenting for emergency care. Methods Structured interviews that included health li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 22 publications
4
82
1
4
Order By: Relevance
“…28,29 Baker and colleagues demonstrated a relationship of health literacy with cardiovascular mortality. 30 Schumacher and colleagues 31 found that patients with low health literacy had fewer doctor office visits (OR 0.6, 95% CI 0.4–1.0), greater emergency department use, OR 1.6; 95% CI, 1.0–2.4), and had more potentially preventable hospital admissions (OR 1.7; 95% CI, 1.0–2.7) than those with adequate health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Baker and colleagues demonstrated a relationship of health literacy with cardiovascular mortality. 30 Schumacher and colleagues 31 found that patients with low health literacy had fewer doctor office visits (OR 0.6, 95% CI 0.4–1.0), greater emergency department use, OR 1.6; 95% CI, 1.0–2.4), and had more potentially preventable hospital admissions (OR 1.7; 95% CI, 1.0–2.7) than those with adequate health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Higher rates of inappropriate ED utilization can lead to a variety of poorer health outcomes such as decreased preventive care services receipts, increased inpatient hospitalizations, lower satisfaction with health care, and higher health care costs. 2,3 National data show that one in five adult Americans (20.1%) utilized emergency room services in the last 12 months with this proportion varying on the basis of age, gender, race, educational achievement, income and status.…”
Section: Introductionmentioning
confidence: 99%
“…oikea-aikainen pääsy terveysaseman vastaanotolle, ikä, sosioekonominen asema, ja potilaan työntekijän väli-nen vuorovaikutus (35). Lisäksi lisääntyneeseen päivystyksen käyttöön ovat yhteydessä myös kyky ymmärtää ja tulkita omaa terveyttä koskevaa informaatiota ja tehdä omia elintapoja, terveyttä ja terveyspalvelujen käyttöä koskevia päätöksiä (36). Terveyspalvelujen kehittämiseksi tarvitaan tietoja siitä, miten eri väestöryhmien kyky vastaanottaa, ymmärtää ja tulkita omaa terveyttään koskevia tietoja voidaan ottaa huomioon sekä miten voidaan auttaa eri väestöryhmiä tekemään elintapoja ja terveyspalvelujen käyttöä koskevia päätöksiä.…”
Section: Pohdintaunclassified